Preparation, performances and application of carbon-ceramic brake discs - Tan Hong; Shen Fuqiang; Li Hulin (Processing and Application of Ceramics)
Carbon-ceramic brake discs, known for their superior mechanical properties and thermal stability, are pivotal in high-performance braking systems. This paper reviews their development, focusing on preparation methods, performance features and applications in aviation, automotive and rail sectors. Made from carbon fibres and silicon carbide, these discs undergo complex manufacturing processes like carbonization and silicification, leading to excellent friction performance, wear resistance and thermal shock resilience. As manufacturing technology progresses and costs decrease, their use is expected to expand significantly. The paper also explores potential optimizations and future roles of carbon-ceramic discs in improving transportation safety and environmental sustainability.